Penguatan Manajemen Kinerja Sumber Daya Manusia dalam Mendukung Keberlanjutan Usaha UMKM Gerakan Pemuda Ansor Kecamatan Pagedangan Kabupaten Tangerang - Endang Susilo Wardani; Laila Irawati; Eti Ariyanti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an essential role in sustaining local economic resilience, including those managed by youth organizations such as Gerakan Pemuda Ansor in Pagedangan District, Tangerang Regency. However, limited human resource management capabilities often hinder business sustainability and performance improvement. This community service program aimed to strengthen human resource performance management to support the sustainability of MSME businesses managed by the Gerakan Pemuda Ansor. Methods were implemented at Balai Desa Cicalengka Pagedangan District Tangerang Regency on May 19, 2026, involving three lecturers from Universitas Pamulang as facilitators and 32 participants from the Gerakan Pemuda Ansor. The PKM activities were carried out through preparation implementation and reporting stages using lectures hands-on practice group discussions and question-and-answer sessions. Results showed that participants gained improved understanding of human resource performance management particularly in planning organizing and evaluating MSME business activities which contributed to increased awareness of sustainable business practices. The program is expected to enhance the sustainability of MSME organizations under Gerakan Pemuda Ansor by improving managerial competence encouraging continuous capacity building and strengthening collaboration between academic institutions and community groups for long term economic empowerment in the Pagedangan District area with sustainable community development outcomes in practice implementation.